Pendidikan Karakter Bagi Generasi Muda Tingkat Sekolah Dasar - Nabila Hilmy Zhafira; Cut Devi Maulidasari; Yenny Ertika; Damrus Damrus; Muhammad Rahmat Hidayat (Universitas Teuku Umar, 2023)
Indonesia is a developing country that has civilization, customs and noble culture that must prioritize noble values. Values such as decency, tenacity, religion, and ethics form the foundation of nation building. Unfortunately these values are increasingly eroded along with the progress of time. Society tends to ignore the values that shape the character of the nation, and is increasingly becoming an individualist, materialist and hedonic society. The challenges that will be faced by the nation in the future are increasingly complex and uncertain, such as the increasing number of unpleasant incidents, crime rates, immorality, and various other dishonest behaviors in society. This is as a result of a lack of understanding and application of moral values. Lack of understanding of moral values and character education makes children only intelligent but without character. National character building cannot be done in a short time and by a handful of people. This character building is a long process that is continuous and requires the participation of all levels of society with their respective roles. One of the efforts that can be made in order to support character building is through educational institutions as agents of change. Students should be equipped with character education so that later they can balance their academic knowledge. This is in line with the issuance of government regulations through the Strengthening Character Education program. through this activity we are trying to take part by providing short education to the younger generation at the elementary school level, especially at SD N 1 Ranto Panyang. Through interactive discussion activities we seek to instill moral values and measure participants' abilities as feedback. from the results obtained, there was an increase in understanding before and after being given the material and discussing it. our hope is that this can be done on an ongoing and massive basis to get even better results in the future.